Structure Refinement of Five Layers Aurivillius Compound: Ba4Bi2Nb2Ti3O18 - Ismu, Ismunandar; Mikrianto, Edi (ITB Journal Publisher, LPPM ITB, 2004)
The room temperature structures of the five layers Aurivillius phase Ba4Bi2Nb2Ti3O18 has been refined from X-ray powder diffraction data using the Rietveld method. The structures consist of [Bi2O2]2+ layers interleaved with perovskite-like [Ba4Nb2Ti3O16]2- blocks. The oxides was found to be orthorhombic (SG B2cb); a = 5.5017(8), b = 5.5031(8), c = 50.363(3) Ã , Rp = 25.53 Rwp = 35.54 Rexp = 29.30 RBragg = 9.92. The structural features of the compound is found similar to that of other layered Aurivillius compounds. Using the available structural data the ferroelectric properties could be explained and strategies to find good ferroelectric materials could be inferred.